Expression Profiling Of Human Presenilins - RASAPPAN PERIANNAN,; SAMPOORNAM BALAKRISHNAN,; ZENITH KHASHIM,; THANIGAIVELAN KANAGASABAI,; THOLCOPIYAN LOGANATHAN,; SHILA SAMUEL, (International Journal of Pharma and Bio Sciences, 2012)
Alzheimer's disease (AD), is the most common form of dementia caused by abnormal fragmentation of amyloid precursor protein by presenilins of γ_secretase protease complex. There are 2 types of presenilins called 1 and 2 and each exists in 2 isoforms. The aim of this study was to get the presenilin sequences from the protein data base and to study functional motifs using motif scan tool and to interpret their functions by computational methods. Motif scan tool identified motifs in presenilin 1 viz., Asn_Glycosylation, Camp_Phospho_Site, Ck2_Phospho_Site, Myristyl, Pkc_Phospho_Site,Arteri_GP4, Coq4,NADHDh, Presenilin c4dic_mal_tran, Oxidored_q5_N. Motifs identified in presenilin 2 were Asn_Glycosylation, Ck2_Phospho_Site, Myristyl, Pkc_Phospho_Site, Arteri_GP4, Presenilin. Clustal W results showed both presenilin 1 and 2 have 65% identical sequences.